Using eDNA to elucidate Silver and Bighead Carp range expansion in two Missouri River tributaries in eastern South Dakota - Labrie, Lindsey A P; Wesner, Jeff S; Britten, Hugh B (bioRxiv, 2023)
This study used environmental DNA (eDNA) to detect Bighead Carp (Hypophthalmichthys nobilis) and Silver Carp (H. molitrix) above and below barriers to fish movement in two tributaries of the Missouri River in eastern South Dakota. The barriers consisted of a natural chain of waterfalls in Sioux Falls in the Big Sioux River and a spillway at the downstream end of Lake Vermillion in the Vermillion River. A total of 213 samples and 38 field blanks were collected over two years (2021/2022). We used filtration methods to collect carp eDNA from the water and qPCR techniques to quantify the amount of eDNA in each sample. The probability of detecting eDNA below the barrier in the Big Sioux River was 51% (95% Credible Interval (CrI): 2 to 97%) and 77% (95% CrI: 8 to 99%) in the Vermillion River. The probability of detecting eDNA above both barriers was significantly smaller: 1% (95% CrI: 0.02 to 24%) for both rivers, with positive above-barrier samples detected only from one sampling date in the Vermillion River. The detection of positive samples above the spillway barrier in the Vermillion River provides the first evidence that Bighead and Silver Carp may have expanded their range to habitats upstream of their documented range in eastern South Dakota. This study demonstrates the utility of using eDNA to detect Bighead and Silver Carp both in areas of known and unknown invasive carp presence in smaller tributary streams to the Missouri River.Competing Interest StatementThe authors have declared no competing interest.Footnotes* updated abstract and title page formatting, added impact, ethics, and COI statements* https://github.com/lindseylabrie/carp_eDNA